"Todo mundo fala mal, mas todo mundo vê" : estudo comparativo do consumo de telenovela por mulheres de diferentes classes - Sifuentes, Lírian (2014)
This study aims to comprehend the role of social class in consumption and social uses of media and telenovela by women from different social groups. The classes considered here are called middle class, ―battler‖ and ―fighter‖. The justifications for this study emphasize the partial lack of studies in Communication with a focus on social class variable. Furthermore, the concept of "new middle class" best defined as new working-class is taken without question by studies of the area and do not contribute in the analysis of media consumption by that public, if not by a marketing bias. The knowledge of the concept of social class, as well as habitus and capital, comes from the reflections of Bourdieu and Souza. Thus, it is possible to have a better comprehension about the relevance of class belonging for media appropriation by the public, in this case, 12 women, four of each social class, living in Porto Alegre region, aged between 27 and 37 years. The research was conducted over 10 months and made use of the instruments in-depth interview, form and observation. It was analyzed the study of modes of individual and social class living; mapping of individual and social class media consumption; and examination of the readings of the telenovela, especially in relation to the analysis of representations of class and gender, individual and class. After it was realized the comparative study between the three classes on each of the three axes. The results point to a substantial difference analyzes of telenovela according to the accumulated cultural capital. The middle class, the group with higher cultural capital, takes readings more critical about the telenovela, both in relation to representations of class and gender. Moreover, this group, along with the ―battlers‖, has a much higher knowledge about the grammar of telenovela than the ―fighters‖. In other aspects, the readings of the different classes converge, as in the statement of the representative character of the typical Brazilian woman, in which responses did not vary from one class to another. Finally, the comparative method to the study of social class and consumption and social use of telenovela proved to be significant, and it can capture important features of each group in relation to their ways of living and watch the media and the telenovela.